The cystine/glutamate antiporter system x(c)(−) drives breast tumor cell glutamate release and cancer-induced bone pain - Slosky, Lauren M. (Pain, 2016)
Bone is one of the leading sites of metastasis for frequently diagnosed malignancies, including those arising in the breast, prostate and lung. Although these cancers develop unnoticed and are painless in their primary sites, bone metastases result in debilitating pain. Deeper investigation of this pain may reveal etiology and lead to early cancer detection. Cancer-induced bone pain (CIBP) is inadequately managed with current standard-of-care analgesics and dramatically diminishes patient quality of life. While CIBP etiology is multifaceted, elevated levels of glutamate, an excitatory neurotransmitter, in the bone-tumor microenvironment may drive maladaptive nociceptive signaling. Here, we establish a relationship between the reactive nitrogen species peroxynitrite, tumor-derived glutamate, and CIBP. In vitro and in a syngeneic in vivo model of breast CIBP, murine mammary adenocarcinoma cells significantly elevated glutamate via the cystine/glutamate antiporter system x(c)(−). The well-known system x(c)(−) inhibitor sulfasalazine significantly reduced levels of glutamate and attenuated CIBP-associated flinching and guarding behaviors. Peroxynitrite, a highly reactive species produced in tumors, significantly increased system x(c)(−) functional expression and tumor cell glutamate release. Scavenging peroxynitrite with the iron and mangano-based porphyrins, FeTMPyP and SRI10, significantly diminished tumor cell system x(c)(−) functional expression, reduced femur glutamate levels and mitigated CIBP. In sum, we demonstrate how breast cancer bone metastases upregulate a cystine/glutamate co-transporter to elevate extracellular glutamate. Pharmacological manipulation of peroxynitrite or system x(c)(−) attenuates CIBP, supporting a role for tumor-derived glutamate in CIBP and validating the targeting of system x(c)(−) as a novel therapeutic strategy for the management of metastatic bone pain.